Are international organizations agents in their own right? A plural subject perspective - Cupać, Jelena (International theory, 2025)
The paper advances a novel theoretical perspective on the agency of international organizations (IOs). It argues that existing accounts–whether focused on intraorganizational actors such as bureaucracies or on member-dominated IOs–overlook the fact that IO agency is inseparable from their personification through the ascription, in decision-making and official documents, of various intentions, beliefs, and emotions. To address this gap, the paper draws on Margaret Gilbert’s concept of plural subjects, i.e., collective agents formed through the joint commitment of their members to act as aunified body. Using the UN Security Council as an illustrative case, the paper contends that IOs function as such plural subjects. In doing so, the paper departs from the longstanding criterion in International Relations that IOs must act independently of state interests and preferences to qualify as agents in their own right. It further argues, also contra dominant theories, that IO agency is not transient, but a stable and enduring feature. The paper concludes by outlining the theoretical and empirical implications of this perspective, particularly for understanding institutional moral agency and IO authority.